New Insights Into the Seasonal Movement Patterns of Shortfin Mako Sharks in the Gulf of Mexico - Gibson, Kesley J.; Streich, Matthew K.; Topping, Tara S.; Stunz, Gregory W. (Frontiers in Marine Science, 2021)
Highly mobile apex predators such as the shortfin mako shark (mako shark; Isurus oxyrinchus) serve an important role in the marine ecosystem, and despite their declining populations and vulnerability to overexploitation, this species is frequently harvested in high abundance in both commercial and recreational fisheries. In 2017, the North Atlantic stock was deemed overfished and to be undergoing overfishing and was recently listed in CITES Appendix II. Effective management of this species requires detailed information on their movements and habitat use, which is lacking, especially in the Gulf of Mexico, a potential mating and parturition ground. In this study, we used satellite telemetry to track the movements of mako sharks in the western Gulf of Mexico between 2016 and 2020. In contrast to previous studies that have primarily tagged juvenile mako sharks (>80% juveniles), ~80% of sharks tagged in this study (7 of 9) were presumed to be mature based on published size-at-maturity data. Sharks were tracked for durations ranging from 10 – 887 days (mean = 359 days; median = 239 days) with three mature individuals tracked for >2 years. Mako sharks tagged in this study used more of the northwestern Gulf of Mexico than reported in previous movement studies on juveniles, suggesting potential evidence of size segregation. While one mature female remained in the Gulf of Mexico over a >2-year period, predominantly on the continental shelf, two mature males demonstrated seasonal migrations ~2,500 km from the tagging location off the Texas coast to the Caribbean Sea and northeastern U.S. Atlantic coast, respectively. During these migrations, mako sharks traversed at least 12 jurisdictional boundaries, which also exposed individuals to varying levels of fishing pressure and harvest regulations. Movement ecology of this species, especially for mature individuals in the western North Atlantic, has been largely unknown until recently. These data included here supplement existing information on mako shark movement ecology and potential stock structure that could help improve management of the species, especially given the prescribed long-term rebuilding plan and the bleak predictions for stock recovery even if no retention policies were adopted throughout the fishery.